Suplementasi Heit-Chrose pada Pakan Sapi Perah Pre-Partum Ditinjau dari Profil Darah dan Recovery Bobot Tubuh Post-Partum - Caribu Hadi Prayitno; Restuti Fitria; Muhamad Samsi (Agricultural Faculty, 2014)
(Pre-partum supplementation of heit-chrose on post-partum blood profile and recovery of body weight of dairy cows)ABSTRACT. This study aimed to determine the profile of blood, metabolic enzymes and recovery of body weight in dairy cows fed diet supplemented with Heit-CHrose (Feed supplement containing saponins, allicin, organic mineral: Se, Cr, and Zn). The experiments were conducted with 4 treatments, R0 : control diet (CP 13,79% and TDN 67,2%), R1 : R0 supplemented with organic minerals (Cr 1,5 ppm; Se 0,3 ppm; Zn-Lyzinat 40 ppm), R2 : Ro supplemented with Heit-CHrose are given in the component feeding, and R3 : Ro supplemented with Heit-CHrose are given in total mixed ration (TMR). Data were tested using analysis of variance with a completely randomized design using four replications, and HSD test. The results showed that the supplementation of Heit-CHrose to the diet of dairy cows gave significant effect (P 0.01) on blood glucose and recovery of body weight, but had no effect (P 0.05) on hemoglobin, blood urea nitrogen (BUN), total protein and blood cholesterol and metabolic enzyme (alkali phospatase). Supplementation of Heit Chrose in dairy cows diet with component feeding and TMR increases blood glucose and recovery of body weight.